2022
DOI: 10.1111/jpn.13702
|View full text |Cite
|
Sign up to set email alerts
|

Use of tannin extract as a strategy to reduce methane in Nellore and Holstein cattle and its effect on intake, digestibility, microbial efficiency and ruminal fermentation

Abstract: This study was carried out to evaluate the use of tannin extract from Acacia mearnsii as a strategy to reduce methane (CH4) in two distinct cattle genotypes and its effect on intake, digestibility, microbial efficiency and ruminal fermentation. Four Nellore (Bos indicus) and four Holstein (Bos taurus) dry cows fitted with rumen cannula were assigned to two 4 × 4 Latin square design, in a 2 × 4 factorial arrangement, where each genotype represented a square receiving four tannin levels (commercial extract of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although in the present study DMI increased by about 7% between growing and fattening periods (data from methane collection periods), CH 4 emission only increased about 3% in bulls fed with TAN vs. CON between these periods. Several studies have reported the positive effects of tannin-based additives in decreasing CH 4 emissions by ruminants ( Min et al, 2020 ; Orzuna-orzuna et al, 2021 ; Fitri et al, 2022 ; Perna Junior et al, 2022 ). Plant tannins have a recognized effect on the gut microbiota through their antibacterial activity ( Tong et al, 2022 ), where this effect is hypothesized due to its interaction with specific substrates, such as protein and bacterial cell walls ( Bae et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although in the present study DMI increased by about 7% between growing and fattening periods (data from methane collection periods), CH 4 emission only increased about 3% in bulls fed with TAN vs. CON between these periods. Several studies have reported the positive effects of tannin-based additives in decreasing CH 4 emissions by ruminants ( Min et al, 2020 ; Orzuna-orzuna et al, 2021 ; Fitri et al, 2022 ; Perna Junior et al, 2022 ). Plant tannins have a recognized effect on the gut microbiota through their antibacterial activity ( Tong et al, 2022 ), where this effect is hypothesized due to its interaction with specific substrates, such as protein and bacterial cell walls ( Bae et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the level of CT found here for all treatments was below this value, no negative effect was seen on the consumption of the diet, as other authors have shown when using diets with similar CT contents, irrespective of the plant used [ 54 , 55 , 56 , 57 ]. In addition, according to Perna Junior et al [ 58 ], values of around 20 to 45 g CT/kg DM are sufficient to interfere in the digestive process of ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CH4 mitigation by CT both in vitro and in vivo is related to a decrease of methanogenic Archaea communities (TAVENDALE et al, 2005;BHATTA et al, 2009;TAN et al, 2011;CIESLAK et al, 2012;TSEU et al, 2020;PERNA JUNIOR et al, 2022). Tan et al (2011) found that a CT inclusion of 20 to 31 60 g kg -1 DM resulted in a linear reduction in total methanogens with a corresponding decrease in CH4 production.…”
Section: Enteric Ch4 Rumen Microbiota and Tanninsmentioning
confidence: 99%